Persepsi Masyarakat Negeri Rumah Tiga Terkait dengan Vaksinasi Covid-19 Ditinjau dari Hak Asasi Manusia - Yohana Lamere; Fricean Tutuarima; Ridwan Hatala (Ideas Publishing, 2022)
This study is a qualitative descriptive study that aims to find out how the public perception of the Negeri Rumah Tiga regarding the covid-19 vaccination is viewed from the point of view of human rights. This research was conducted in Negeri Tiga Rumah, Teluk Ambon District. Primary data collection was carried out through interviews with a number of informants who were directly involved. The results of this study can show that the people of Negeri Tiga Rumah have different perspectives about the covid-19 vaccination. The people of Negeri Tiga view watching covid-19 with different glasses, there are people who consider the covid-19 vaccination as something that is very necessary to do considering the covid-19 virus that is currently circulating, but there are also many people who do not support the implementation of the covid-19 vaccination. 19 and that refusing to be vaccinated against covid-19 is a form of their right and they consider that mandatory Covid-19 vaccination is a violation of human rights. And they assess that the Covid-19 vaccination can only have a bad impact on the community and even with the Covid-19 vaccine, the community is complicated in all arrangements because there is no vaccine card. Thus, the role of the local government is very much needed in hoping the community will be aware of the importance of the Covid-19 vaccination.